(untitled) (UUM Journal of Legal Studies, 2022)
The enactment of the Prevention of Terrorism Act 2015 (POTA) in Malaysia has led to numerous detentions and rulings that are arguably violations of human rights. Through an analysis of primary and secondary materials, viz., the Federal Constitution of Malaysia, court decisions and relevant statutes, this paper questions the necessity of such draconian preventive detention legislation as POTA and concludes that a valid concern for national security has infringed the rights of Malaysian citizens. Thus, POTA must be re-evaluated and re-examined to ensure that the Malaysian government defends the traits that differentiate them from the terrorists they are combating.